2014
DOI: 10.1371/journal.pone.0108453
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Translocation of Clinical Isolates of Vancomycin-Resistant Enterococcus faecalis and ESBL-Producing Escherichia coli in a Rat Model of Bacterial Colonization and Liver Ischemia/Reperfusion Injury

Abstract: The objectives of this study were to develop a rat model of gastrointestinal colonization with vancomycin-resistant Enterococcus faecalis (VRE) and extended-spectrum beta-lactamase (ESBL)-producing E. coli and to evaluate intestinal translocation to blood and tissues after total and partial hepatic ischemia. Methods - We developed a model of rat colonization with VRE and ESBL-E coli. Then we studied four groups of colonized rats: Group I (with hepatic pedicle occlusion causing complete liver ischemia and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…Although they came from the same species, translocated strains and non-translocated strains differed clearly in terms of the ERIC2-PCR and RAPD-PCR patterns (77.5 % of strains). As reported in the literature [26], we concluded that BT did not occur in samples when the extra-intestinal organs (liver, spleen, Peyer’s patches, MLNs, adipose tissue, and kidneys) were sterile. One could argue that the intestinal bacteria found in the extra-intestinal tissue samples resulted from bacterial contamination and not from BT.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although they came from the same species, translocated strains and non-translocated strains differed clearly in terms of the ERIC2-PCR and RAPD-PCR patterns (77.5 % of strains). As reported in the literature [26], we concluded that BT did not occur in samples when the extra-intestinal organs (liver, spleen, Peyer’s patches, MLNs, adipose tissue, and kidneys) were sterile. One could argue that the intestinal bacteria found in the extra-intestinal tissue samples resulted from bacterial contamination and not from BT.…”
Section: Discussionsupporting
confidence: 61%
“…Although molecular typing has often been used to characterized BT in a clinical setting [24, 25], there are few literature data on the use of these techniques to detect translocation from the intestinal tract in animal models [26]. To the best of our knowledge, the present study is the first to have employed molecular typing (ERIC2-PCR and RAPD-PCR) techniques in the detection of BT in the rat.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, patient feces are contaminated with VRE, leading to the development of exogenous infections 5 . Therefore, in the control and prevention of the spread of VRE infections, it is important to timely detect patients with VRE colonization, elucidate their relationship with hospital infection outbreaks, and identify virulence factors for colonization and infection 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…E. faecalis ranks as the fourth most important cause of hospital-acquired infections and the third leading cause of bacteremia, where its intrinsic or acquired antibiotic resistance contributes to its pathogenicity [2]. Recent evidence suggests that E. faecalis has a remarkable ability to translocate from the GI to reach the bloodstream and colonize distant anatomical locations [3][4][5][6]. For instance, in patients treated with antibiotics during allogeneic hematopoietic stem cell transplantation, colonization of the intestinal tract by antibiotic-resistant enterococci has been observed prior to the emergence of bloodstream infections [4].…”
mentioning
confidence: 99%
“…For instance, in patients treated with antibiotics during allogeneic hematopoietic stem cell transplantation, colonization of the intestinal tract by antibiotic-resistant enterococci has been observed prior to the emergence of bloodstream infections [4]. Moreover, the use of broad-spectrum antimicrobials has been suggested to be a predisposing factor that promotes the translocation of vancomycinresistant enterococci [5]. While the mechanisms of enterococcal migration remain largely unexplored, recent evidence indicates that this process is mediated by the formation of bacterial aggregates through cellsurface appendages, adhesins, and other unknown factors [4][5][6][7][8][9][10].…”
mentioning
confidence: 99%